2021
DOI: 10.1029/2021ja029742
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Lobe Reconnection Rate During Dominant IMF By Periods and Different Dipole Tilt Orientations

Abstract: Lobe reconnection is usually thought to play an important role in geospace dynamics only when the Interplanetary Magnetic Field (IMF) is mainly northward. This is because the most common and unambiguous signature of lobe reconnection is the strong sunward convection in the polar cap ionosphere observed during these conditions. During more typical conditions, when the IMF is mainly oriented in a dawn‐dusk direction, plasma flows initiated by dayside and lobe reconnection both map to high‐latitude ionospheric lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Evidence toward the former hypothesis was provided by Reistad et al. ( 2021 ) who showed that there is an explicit B y ‐dependence in the cross‐polar cap potential which is consistent with a similar B y ‐dependence of the substorm occurrence frequency (Liou et al., 2020 ; Ohma et al., 2021 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Evidence toward the former hypothesis was provided by Reistad et al. ( 2021 ) who showed that there is an explicit B y ‐dependence in the cross‐polar cap potential which is consistent with a similar B y ‐dependence of the substorm occurrence frequency (Liou et al., 2020 ; Ohma et al., 2021 ).…”
Section: Discussionmentioning
confidence: 63%
“…They suggested that IMF B y either modulates the dayside reconnection rate or the magnetotail response to solar wind driving. Evidence toward the former hypothesis was provided by Reistad et al (2021) who showed that there is an explicit B y -dependence in the cross-polar cap potential which is consistent with a similar B y -dependence of the substorm occurrence frequency (Liou et al, 2020;Ohma et al, 2021).…”
Section: Discussionmentioning
confidence: 67%
“…The HiLDA spot/space hurricane is clearly visible in the WIC image displayed in Figure 9 . It is a signature of lobe reconnection during times when the interplanetary magnetic field has a strong positive B y component (or negative, if observed in the Southern hemisphere; Reistad et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The HiLDA spot/space hurricane is clearly visible in the WIC image displayed in Figure 9. It is a signature of lobe reconnection during times when the interplanetary magnetic field has a strong positive B y component (or negative, if observed in the Southern hemisphere; Reistad et al, 2021). The magnetic field components measured by CHAMP (with the International Geomagnetic Reference Field (IGRF) main magnetic field subtracted), as solid lines.…”
Section: A High-latitude Dayside Aurora Eventmentioning
confidence: 99%
“…A large region surrounding the magnetic poles do not connect to the opposite hemisphere but instead connect out in the solar wind. In these regions of open magnetic flux (the polar caps), we expect to see mismatches in the potentials (Crooker and Rich, 1993;Reistad et al, 2019Reistad et al, , 2021 that are unrelated to magnetic field line displacements. In regions that map to reconnection, we also expect there to be magnetic fieldaligned potential differences between hemispheres (Siscoe et al, 2001).…”
Section: Inversionmentioning
confidence: 99%